Inoculation With Piriformospora indica Is More Efficient in Wild-Type Rice Than in Transgenic Rice Over-Expressing the Vacuolar H+-PPase - Bertolazi, Amanda Azevedo; de Souza, Sávio Bastos; Ruas, Katherine Fraga; Campostrini, Eliemar; de Rezende, Carlos Eduardo; Cruz, Cristina; Melo, Juliana; Colodete, Carlos Moacir; Varma, Ajit; Ramos, Alessandro Coutinho (Frontiers in Microbiology, 2019)
Achieving food security in a context of environmental sustainability is one of the main challenges of the XXI century. Two competing strategies to achieve this goal are the use of genetically modified plants and the use of plant growth promoting microorganisms (PGPMs). However, few studies assess the response of genetically modified plants to PGPMs. The aim of this study was to compare the response of rice plants over-expressing the vacuolar H+-PPase (AVP) to the endophytic fungus Piriformospora indica with the response of unmodified plants (WT). Oryza sativa plants (WT and AVP) were inoculated with P. indica and 30 days later, morphological, ecophysiological and bioenergetic parameters, and nutrient content were assessed. AVP and WT plant heights were strongly influenced by inoculation with P. indica, which also promoted increases in fresh and dry matter of shoot in both genotypes. This may be related with the stimulatory effect of P. indica on ecophysiological parameters, especially photosynthetic rate, stomatal conductance, intrinsic water use efficiency and carboxylation efficiency. However, there were differences between the genotypes concerning the physiological mechanisms leading to biomass increment. In WT plants, inoculation with P. indica stimulated all H+ pumps. However, in inoculated AVP plants, H+-PPase was stimulated, but P- and V-ATPases were inhibited. Fungal inoculation enhanced nutrient uptake in both shoots and roots of WT and AVP plants; but in inoculated genotypes, the nutrient uptake was lower in AVP than in WT plants. These results clearly demonstrate that the symbiosis between P. indica and AVP plants did not benefit those plants, which may be related to the inefficient colonization of this fungus on the transgenic plants, demonstrating an incompatibility of this symbiosis, which needs to be further studied.